2000
DOI: 10.1165/ajrcmb.23.4.3944
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Hyaluronan in Macrophage Accumulation and Collagen Deposition after Bleomycin-Induced Lung Injury

Abstract: Elevated concentrations of hyaluronan (HA) are associated with the accumulation of macrophages in the lung after injury. We have investigated the role of HA in the inflammatory and fibrotic responses to lung injury using the intratracheal instillation of bleomycin in rats as a model. After bleomycin-induced lung injury, both HA content in bronchoalveolar lavage (BAL) and staining for HA in macrophages accumulating in injured areas of the lung were maximal at 4 d. Increased HA in BAL correlated with increased l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 68 publications
4
74
1
Order By: Relevance
“…This reagent has been used previously to bind HA and attenuate the biological effects of this molecule (16). Immunohistochemical staining demonstrated that HABP significantly attenuated CD44-hyaluronan binding on alveolar macrophages after ozone exposure, compared with scrambled control peptide or saline (Fig.…”
Section: Ha Recognition Is Required For the Development Of Ahr Aftermentioning
confidence: 94%
“…This reagent has been used previously to bind HA and attenuate the biological effects of this molecule (16). Immunohistochemical staining demonstrated that HABP significantly attenuated CD44-hyaluronan binding on alveolar macrophages after ozone exposure, compared with scrambled control peptide or saline (Fig.…”
Section: Ha Recognition Is Required For the Development Of Ahr Aftermentioning
confidence: 94%
“…[28][29][30][31] CD44 has been shown to have an important role in the clearance of HA from the airways during bleomycin-or LPS-induced lung inflammation, 8,12 and the accumulation of HA fragments contributes to the perpetuation of inflammation in these models. 12,32 Therefore, we considered it of interest to investigate whether CD44 has a part in the clearance of HA during the resolution phase of S. pneumoniae-induced pneumonia. Indeed, HA levels measured in BALF obtained at 4 or 10 days after sublethal infection were much higher in CD44 KO mice than in WT mice ( Figure 5).…”
Section: Cd44 Deficiency Is Associated With Accumulation Of Ha Fragmementioning
confidence: 99%
“…Peptides-HA-binding peptide (HABPep), mimicking a charged sequence previously shown to bind HA (RGG-GRGRRR) (25) and scrambled peptide containing the same amino acids but in a random, non-HA binding order (RGRRGRGRG), have been described previously (14). Peptides were commercially produced to ÏŸ95% purity (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…12). An increased recovery of HA in bronchoalveolar lavage has been found in a variety of human lung disorders, such as acute respiratory distress syndrome and occupational lung disorders, and in animal models, such as bleomycin-induced lung injury (13,14). In this rodent model, elevated low molecular weight HA content in bronchoalveolar lavage temporally correlates with an influx of macrophages into the lung.…”
mentioning
confidence: 89%
See 1 more Smart Citation